Non-cytotoxic Dityrosine Photocrosslinked Polymeric Materials With Targeted Elastic Moduli - Camp, Christopher P.; Peterson, Ingrid L.; Knoff, David S.; Melcher, Lauren G.; Maxwell, Connor J.; Cohen, Audrey T.; Wertheimer, Anne M.; Kim, Minkyu (Frontiers in Chemistry, 2020)
Controlling mechanical properties of polymeric biomaterials, including the elastic modulus, is critical to directing cell behavior, such as proliferation and differentiation. Dityrosine photocrosslinking is an attractive and simple method to prepare materials that exhibit a wide range of elastic moduli by rapidly crosslinking tyrosyl-containing polymers. However, high concentrations of commonly used oxidative crosslinking reagents, such as ruthenium-based photoinitiators and persulfates, present cytotoxicity concerns. We found the elastic moduli of materials prepared by crosslinking an artificial protein with tightly controlled tyrosine molarity can be modulated up to 40 kPa by adjusting photoinitiator and persulfate concentrations. Formulations with various concentrations of the crosslinking reagents were able to target a similar material elastic modulus, but excess unreacted persulfate resulted in cytotoxic materials. Therefore, we identified a systematic method to prepare noncytotoxic photocrosslinked polymeric materials with targeted elastic moduli for potential biomaterials applications in diverse fields, including tissue engineering and 3D bioprinting.